The Order of Convergence of Difference Schemes for Fractional Equations. (3rd June 2017) - Liu, Ru; Li, Miao; Piskarev, Sergey
ABSTRACT: In this paper, we continue our research on convergence of difference schemes for fractional differential equations. Using implicit difference scheme and explicit difference scheme, we have a deal with the full discretization of the solutions of fractional differential equations in time variables and get the order of convergence.